Environmental Degradation in Asia Land Degradation, Environmental Contamination, and Human Activities - Al-Quraishi, Ayad M. Fadhil; Mustafa, Yaseen T.; Negm, Abdelazim M. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This unique book focuses on environmental degradation in Asian countries including land degradation and soil erosion. The land degradation covers assessing environmental degradation using geospatial technology, land use land cover mapping, environmental and anthropogenic degradation, assessment of land degradation vulnerability, evaluation of the impact of earthquake and the environmental control of the sand dunes. It also addresses the soil degradation and environmental pollution and presents several case studies such as tectonic activity and erosion, assessment of aircraft sound, soil degradation assessment for the arid territories, soil pollution, waste engine oil contamination, soil degradation, soil erosion modelling, land use and land cover change and its effect on soil erosion changes. Additionally, the book discusses the impact of climate change, and human activities including urban environmental quality, air pollution and the impact of armed conflict on the environment. Moreover, topics such as vegetation degradation including forest changes, hydrological and agricultural drought are presented. The book includes authors and scientists from Egypt, Iraq, Iran, India, Mongolia, United Arab Emirates, Uzbekistan, Republic of Kazakhstan, USA, Turkey, South Africa, Italy, China, Malaysia, Poland and Russia. Graduate students, researchers, engineers, policy planners, policymakers and stockholders could benefit from the information and the knowledge in this book.
Chapter 1. Introduction (Ayad M. Fadhil Al-Quraishi) -- Part I: Land Degradation -- Chapter 2. Assessing Environmental Degradation using Geo-spatial Technology: A Case Study (Arnab KUNDU) -- Chapter 3. Land Use Land Cover mapping using optimized Multi-layer Perceptron algorithm (Ali Jamali) -- Chapter 4. Environmental Degradation of Mongolia from 1990 to 2019 using Landsat, MODIS, AVHRR Data, and Machine Learning Technique (Otgonbayar Munkhdulam) -- Chapter 5. Assessment of Land Degradation Vulnerability Using GIS-Based Multi-criteria Decision Analysis (MCDA) (Hazhir Karimi) -- Chapter 6. Evaluation of Zarand Earthquake in Central Iran using Satellite images and GIS (Hamid Allahvirdias) -- Chapter 7. Environmental Control of the Sand Dunes in Iraq (Hasan K. Jasim) -- Chapter 8. Assessment of Aircraft Sound on Students' Performance (Khaula Abdulla Saif Alkaabi) -- Chapter 9. Soil Degradation Assessment for the Arid Territories of Kazakhstan (Dmitry V. Malakhov).
Keywords: Environmental management; Environmental monitoring; Human ecology-Study and teaching; Environmental Management; Environmental Monitoring; Environmental Studies